Edukasi Kesiapsiagaan Bencana Erupsi Gunung Merapi Pada Lansia Dan Ibu Hamil Di Desa Kemalang, Balerante, Klaten - Puput Risti Kusumaningrum; Devi Permata Sari; Cahyo Pramono; Farah Choirun Nisa (Universitas Muhammadiyah Klaten, 2024)
The impact of the eruption can result in morbidity and mortality rates, especially in the most high-risk groups, namely children and the elderly who have physical and mental limitations. According to BPBD data in 2023, there have been 774 cases of natural disasters in the form of volcanic eruptions in Indonesia. The impact of disasters on vulnerable groups, namely pregnant women and the elderly, is more severe than other age groups. The methodology in this activity is to measure the level of knowledge before and after being given education about disaster preparedness for the eruption of Mount Merapi for the elderly and pregnant women. In this community service activity, the results obtained before the education were given with knowledge lacking as many as 21 (60%) people, sufficient as many as 9 (25.7%) people, and good as many as 5 (14.3%) people. After being given education, the level of knowledge of respondents increased with knowledge lacking as many as 3 (8.6%) people, sufficient as many as 5 (14.3%) people, and good as many as 27 (77.1%) people. Conclusion: The results after the education can be seen that the respondents' knowledge has increased and this method is considered effective in increasing respondents' knowledge.